"Humanization and technology" on the idea of ​​development and technological progress (2021)
The humanization of the technology understood like a humanistic project, is nor a new version of technology neither a modern revolutionary movement, it symbolizes the vindication with the nature and the recovery of the social being. It is not only wanted to go with technology beyond the use and the mechanization of the technological instrument, but also to rescue the notion of technological development based on the idea of “ progress ”, coming up from Church and having it been latent like one of the contemporary issues that are revealed from Vatican Council II, in its main constitution in Gaudium et Spes, which is a valid document debating not only the problems of the humanity but also the problems of the mankind creation and his instruments, so that “ the man knows very well it is on his hands to direct correctly the forces that has himself triggered, those ones which can devastate or serve him. For that reason it is inquired himself”(GAUDIUM ET SPES, 9).